ChemInform Abstract: Cerium Intermetallics CeTX ‐ Review III. Issue 17 (April 2016) - Poettgen, Rainer; Janka, Oliver; Chevalier, Bernard
Abstract: Review: crystal chemistry, bonding peculiarities, magnetic and transport properties, 119 Sn Moessbauer spectroscopic data, high‐pressure studies, hydrogenation reactions, as well as the formation of solid solutions of CeTX phases with electron‐poor and electron‐rich transition metals (T) and X: Mg, Zn, Cd, Hg, Al, Ga, In, Tl, Si, Ge, Sn, Pb, P, As, Sb, and Bi; 296 refs.